Effect of caffeine on reactive agility time when fresh and fatigued - Duvnjak-Zaknich, D.; Dawson, B. T.; Wallman, K. E.; Henry, G. (Medicine & Science in Sports & Exercise, 2011)
Purpose: This study examined the effects of acute caffeine ingestion on agility performance and decision-making accuracy after simulated team-sport exercise. Methods: Using a randomized, double-blinded, counterbalanced design, 10 moderately trained male team-sport athletes ingested either caffeine (6 mg/kg) or placebo (dextrose) 60 min before completing an 80-min (4 × 20 min) simulated team-game, intermittent running protocol. Interspersed between each exercise quarter was a reactive agility test (RAT) consisting of five trials where measures of total time (TT), reactive agility (RA) time, decision time (DT), movement time (MT), and decision-making accuracy were obtained. Results: Although there were no significant differences between trials for TT (P = 0.54), RA time (P = 0.84), MT (P = 0.89), or DT (P = 0.91), caffeine ingestion resulted in consistently faster TT (2.3%), RA time (3.9%), MT (2.7%), and DT (9.3%) scores compared with placebo (significant main effect for condition for RA time, TT, DT, and MT; P < 0.05). These faster times were supported by qualitative analyses of "almost certain benefit" and large effect size (ES) for RA (quarter 3) and "likely" to "very likely benefits" and moderate to large ES for TT (precircuit and quarters 1, 2, and 4) and RA time (precircuit and quarters 1, 2 and 4). A "likely benefit" and moderate ES was found for MT (quarters 1 and 3), but the effect of caffeine on DT was largely "unclear," with small ES and only a "likely" chance of benefit (quarters 2 and 3). Improved decision-making accuracy (3.8%) after caffeine ingestion was supported by a "likely benefit" (quarter 1) and large ES (quarters 1 and 4). Conclusion: Caffeine ingestion may be beneficial to RA performance when athletes are fresh and fatigued.